The establishment of segmentation in the Drosophila leg. - Rauskolb, C. (Development, 2001)
Segmentation is a developmental mechanism that subdivides a tissue into repeating functional units, which can then be further elaborated upon during development. In contrast to embryonic segmentation, Drosophila leg segmentation occurs in a tissue that is rapidly growing in size and thus segmentation must be coordinated with tissue growth. I demonstrate that segmentation of the Drosophila leg, as assayed by expression of the key regulators of segmentation, the Notch ligands and fringe, occurs progressively and I define the sequence in which the initial segmental subdivisions arise. I further demonstrate that the proximal-distal patterning genes homothorax and dachshund are positively required, while Distal-less is unexpectedly negatively required, to establish the segmental pattern of Notch ligand and fringe expression. Two Serrate enhancers that respond to regulation by dachshund are also identified. Together, these studies provide evidence that distinct combinations of the proximal-distal patterning genes independently regulate each segmental ring of Notch ligand and fringe expression and that this regulation occurs through distinct enhancers. These studies thus provide a molecular framework for understanding how segmentation during tissue growth is accomplished.